The effect of exercise intensity on erythropoietin levels following acute exercise in trained runners - Bodary, P. F.; Pate, R. R.; Wu, Q. F.; Bodary, J. M. (Medicine & Science in Sports & Exercise, 1996)
Well-trained runners (N = 10) were subjected to a variety of exercise bout intensities: high-continuous (90-92% VO2max), high-intermittent, low-continuous (60% VO2max), and rest (control condition). Exercise bouts were one hour and estimated to be of equal energy expenditure. Blood parameters of hemoglobin, hematocrit, red blood cell count, and erythropoietin (EPO) were measured at pre-exercise, and immediately, 4, 12, 24, and 48 hours post-exercise. It was found that neither moderate nor intense exercise altered EPO in trained athletes. Implication: EPO changes are one of the theoretical justifications for altitude training. However, this study showed that such changes are not an outcome of exercise stress. It would appear that EPO is not a factor related to performance changes in already well-trained athletes and therefore, should not be considered as a possible benefit from altitude training.